2022
DOI: 10.4103/lungindia.lungindia_126_21
|View full text |Cite
|
Sign up to set email alerts
|

Taxane-induced acute interstitial pneumonitis in patients with breast cancer and outcome of taxane rechallenge

Abstract: Background: Although rare, taxane-induced interstitial pneumonitis is a well-recognized toxicity following chemotherapy. Data on taxane rechallenge in patients who developed taxane-induced interstitial pneumonitis following chemotherapy are limited. Here, we share our experience of acute interstitial pneumonitis following taxane chemotherapy for breast cancer and its clinical outcome following steroids and subsequent rechallenge with taxanes in selected patients without residual lung abnormalities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
2
9
0
Order By: Relevance
“…The first case series described three patients in which paclitaxel was switched to an alternate agent, nanoparticle albumin-bound paclitaxel, known to be the least likely taxane to cause severe pneumonitis [8,9]. However, a more recent case series of 19 patients described 17 patients being rechallenged with the same inciting taxane and two switched to docetaxel, similar to our patient [6]. Notably, our patient was not put on short-course oral steroids during and following the rechallenge for one week as a safety measure in contrast to the latter [6].…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…The first case series described three patients in which paclitaxel was switched to an alternate agent, nanoparticle albumin-bound paclitaxel, known to be the least likely taxane to cause severe pneumonitis [8,9]. However, a more recent case series of 19 patients described 17 patients being rechallenged with the same inciting taxane and two switched to docetaxel, similar to our patient [6]. Notably, our patient was not put on short-course oral steroids during and following the rechallenge for one week as a safety measure in contrast to the latter [6].…”
Section: Discussionsupporting
confidence: 71%
“…However, a more recent case series of 19 patients described 17 patients being rechallenged with the same inciting taxane and two switched to docetaxel, similar to our patient [ 6 ]. Notably, our patient was not put on short-course oral steroids during and following the rechallenge for one week as a safety measure in contrast to the latter [ 6 ].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…They reported that 49% subjects did not have any recurrence of pneumonia and oral steroids were given to the subjects as a safety measure. 8 The study also advised against re-challenge of drugs in patients with residual lung abnormalities after steroids. A study conducted by Hoshina et al and Takei et al showed an occurrence of case of ild in a patient undergoing treatment with anthracycline induced chemotherapy.…”
Section: Discussionmentioning
confidence: 99%